The Influence of Financing and Mentoring on the Development of MSMEs Under PT. PNM Mekaar in Sungsang Village, Banyuasin Regency - Riri Hanifa; Ria Putri Andriyani; Noprian Noprian; Rikkie Dekas; Anton Trianto (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
This research is motivated by the importance of Micro, Small, and Medium Enterprises (MSMEs) in the national economy, specifically in absorbing labor and improving community welfare. However, many MSME actors still face obstacles in accessing financing and lack sustainable mentoring. PT. PNM Mekaar is present as an institution that provides financing and mentoring to MSMEs, including those in Sungsang Village, Banyuasin Regency. This study aims to analyze the influence of financing and mentoring on the development of MSMEs fostered by PT. PNM Mekaar. The method used is a quantitative approach with multiple linear regression analysis. The population includes all active clients with a minimum mentorship period of 1 year, and a sample of 96 respondents was selected using purposive sampling techniques. Data were collected through questionnaires, interviews, and documentation, then analyzed using validity tests, reliability tests, classical assumption tests, and hypothesis testing (t-test and F-test). The results of the t-test conclude that the financing and mentoring variables have a positive and significant partial influence on MSME development